Food restriction delays breeding and affects insulin-like growth factor-1, oxidative damage, and haematocrit value before egg-laying in female canaries - Hargitai, Rita; Boross, Nóra; Tóth, Zsófia; Lendvai, Ádám (Dryad, 2022)
Environmental challenges, such as fluctuations in food availability, could
influence reproductive investment. If resource availability is poor,
individuals need to decide in which life-history process they invest more
energy and vital compounds, which determine the cost of reproduction. In
resource allocation, the physiological pathways have important roles. The
aim of our study was to examine whether food availability influenced
physiological traits (insulin-like growth factor-1 (IGF-1) concentration,
antioxidant capacity (OXY), level of oxidative damage (ROM) and
haematocrit value) prior to egg-laying in female canaries (Serinus
canaria). We also tested whether these physiological traits were
associated with traits reflecting the reproductive investment in egg
macro- (egg mass and yolk mass) and micronutrient content (eggshell
biliverdin- and protoporphyrin-based colouration). To test these questions
we conducted a food restriction experiment with control and
food-restricted (72% of control food) groups. Our study showed that
food-restricted canary females delayed egg-laying and the physiological
traits differed between the groups. At the pre-laying period, after 9-11
days of treatment, a reduction in plasma IGF-1 concentration, ROM level,
and haematocrit value was detected in the control group, whereas in the
food-restricted group plasma IGF-1 concentration increased, while ROM
level and haematocrit value did not change. Plasma level of OXY was not
influenced by treatment or breeding period. Plasma concentration of IGF-1,
haematocrit value and oxidative status before egg laying did not affect
the egg characteristics. Our study highlights the importance of breeding
stage when studying and interpreting the effects of food restriction on
physiological traits of breeding birds. Moreover, our data suggest that
nutritional limitation had an effect on the timing of egg-laying that
could be mediated by changes in physiological variables.
Keywords: FOS: Biological sciences